The safety and efficacy of vortioxetine for acute treatment of major depressive disorder: a systematic review and meta-analysis - Meeker, Amanda S (Syst Rev, 2015)
BACKGROUND: Vortioxetine is the first mixed serotonin agonist and antagonist antidepressant approved in the US. We sought to evaluate all published and unpublished data available to determine the efficacy and harms of vortioxetine in adults with major depressive disorder. METHODS: We used a predefined search strategy of MEDLINE, the Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, and Drugs@FDA to identify studies evaluating vortioxetine in the acute treatment of major depressive disorder. Only randomized controlled trials (RCTs) that provided results on relevant clinical efficacy and safety outcomes were included. Study quality was assessed and results were pooled using mixed effect meta-analyses where applicable. RESULTS: We identified 11 RCTs with 6,145 participants meeting inclusion criteria (eight were published and three were unpublished). The trials did not exceed 8 weeks in duration. The response rate with vortioxetine was significantly higher for 1-mg (relative risk (RR) = 1.91; 95% confidence interval (CI) 1.36 to 2.69), 5-mg (RR = 1.33; 95% CI 1.10 to 1.61), 10-mg (RR = 1.42; 95% CI 1.21 to 1.67), and 20-mg doses (RR = 1.58; 95% CI 1.19 to 2.08) compared to placebo. Remission rates were significantly higher for the 10-mg group (RR = 1.45; 95% CI 1.18 to 1.77) and the 20-mg group (RR = 1.68; 95% CI 1.19 to 2.37) compared to placebo. Meta-regression of dose on the log odds ratio of response was not statistically significant (β = 0.01; P = 0.46). Vortioxetine response rates were lower than active serotonin and norepinephrine reuptake inhibitor (SNRI) comparators for the 5-mg (RR = 0.88; 95% CI 0.80 to 0.98), 15-mg (RR = 0.78; 95% CI 0.68 to 0.90), and 20-mg (RR = 0.82; 95% CI 0.72 to 0.94) doses. The most common adverse events were nausea and vomiting which increased in frequency with higher doses. CONCLUSIONS: Vortioxetine was significantly more effective than placebo for acute treatment of major depressive disorder (MDD). Although treatment effect estimates varied substantially between studies, a dose effect was not observed. Vortioxetine does not appear to be more effective, and is potentially less effective, than an SNRI. SYSTEMATIC REVIEW REGISTRATION: PROSPERO CRD42013006198. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13643-015-0001-y) contains supplementary material, which is available to authorized users.